Geração de resíduos sólidos domiciliares e a crise hídrica no município de Campina Grande – PB - Barreto Filho, Marcus Aurélio Coutinho (2018)
Solid waste is one of the pillars of waste management, and its importance has become definitive in Brazil since the implementation of Federal Law n° 12.305/2010, regulated by the Decree n° 7.404 of 2010, which instituted the Política Nacional de Resíduos Sólidos (National Policy of Solid Waste - PNRS). This legislation states that solid urban waste (RSU) must encompass both domestic solid waste (RSD) and the waste produced by urban cleaning. Therefore, the waste from commercial establishments and service providers, if characterized as not dangerous, may, according to its own nature, composition or volume, be considered equal to domestic waste by the city administration. Normally, these administrations will charge the population a Taxa de Coleta de Resíduos (Waste Collection Tax - TCR), generally proportional to the size of the real estate. This often leads to injustice, for not always the estate size is directly related to the amount of domestic solid waste produced by its inhabitants. There are works in literature that mention other parameters to verify this relationship, suggesting mathematic models and other indirect parameters, such as water consumption. In any way, there are few studies that prove this phenomenon, especially when considering the entire municipal area. In light of this, this research had the objective of analising the generation of domestic solid waste in the context of the water crisis in the city of Campina Grande, Paraíba, for if there is indeed a relationship of cause and effect between these variables, the present moment is considered opportune for an evaluation. The methodology applied was data collection on the following government bodies: Secretaria de Serviços Urbanos e Meio Ambiente (SESUMA), part of Campina Grande city hall, and Companhia de Água e Esgotos da Paraíba (CAGEPA). The data obtained is on the production of domestic solid waste and monthly domestic water consumption, comprising the period of january 2008 to december 2017. Based on the results, it was possible to observe that water rationing has generated a decrease in the domestic consumption, especially among the consumers paying the Ordinary Consumption Fee (above 10m³). Regarding the production of solid waste, the effect was not the same. Some evidence has been observed, but not enough to ratify an association of cause and effect in the context of the water crisis. It was also possible to observe, in a general way, that political and administrative questions may influence the contractual management of domestic solid waste.